2010
DOI: 10.1002/ptr.3345
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory activity of Phyllanthus emblica, Plumbago zeylanica and Cyperus rotundus in acute models of inflammation

Abstract: Experimental studies conducted earlier have proved that Phyllanthus emblica (Pe), Plumbago zeylanica (Pz) and Cyperus rotundus (Cr), plants from the medohara group of Ayurveda possess antiatherosclerotic activity. As inflammation is also one of the pathophysiological factors, it was of interest to evaluate whether these drugs exhibit any antiinflammatory activity. Two models of acute inflammation, namely carrageenan induced rat paw edema and acetic acid induced peritonitis in mice were used. In the model of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 18 publications
0
57
0
1
Order By: Relevance
“…In the model of carrageenan induced paw edema Cyperus rotundus showed a trend to reduce the edema, whereas in a model of acetic acid induced peritonitis, Cyperus rotundus induced significant decrease in the protein content of the peritoneal exudates compared with the disease control group (p < 0.05) [99]. Clinical studies with 2% aqueous extract of Cyperus rotundus showed anti-inflammatory activity in conjunctivitis in human [100].…”
Section: Antiinflammatory Antipyretic and Analgesic Effectsmentioning
confidence: 99%
“…In the model of carrageenan induced paw edema Cyperus rotundus showed a trend to reduce the edema, whereas in a model of acetic acid induced peritonitis, Cyperus rotundus induced significant decrease in the protein content of the peritoneal exudates compared with the disease control group (p < 0.05) [99]. Clinical studies with 2% aqueous extract of Cyperus rotundus showed anti-inflammatory activity in conjunctivitis in human [100].…”
Section: Antiinflammatory Antipyretic and Analgesic Effectsmentioning
confidence: 99%
“…have been reported for its antioxidant, antipyretic, antimicrobial, anticancer, anti-inflammatory, immunomodulatory, hypolipidemic, and hepatoprotective properties [20][21][22][23][24][25][26][27]. The methanolic extract of P. emblica has been reported for the bacterial efflux pump inhibiting activity [28].…”
Section: Resultsmentioning
confidence: 99%
“…1 P. emblica has been shown to possess anti-inflammatory effects. 2,3 As the current anti-inflammatory agents are known to possess GI related adverse effects, agents which have gastro protective effects are required. In a study published by Bandyopadhyay SK and Shirish SS et al Phyllanthus emblica has shown to have protective effect on gastric ulcer.…”
Section: Introductionmentioning
confidence: 99%